Implementasi Pengembangan Fisik-Motorik Anak Usia Dini Berbasis Kurikulum Merdeka PAUD: Studi Kasus di TK Aisyiyah 2 dan TK Kartika IX-10 Tasikmalaya - Naila Chofia Salsabila; Afrilia Mustika Juniati; Ai Asti Ramjani; Eka Gusriani; Rifa Mahmudah; Risti Apriani (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The study titled Implementation of Physical Motor Development for Early Childhood at TK Aisyiyah 2 and TK Kartika IX-10 Cangkurileung Tasikmalaya aims to describe in depth the implementation of motor stimulation as a foundation for cognitive, socio-emotional, and independent development in early childhood. This research employs a qualitative descriptive method with data collected through participatory observation, semi-structured interviews, and documentation analysis, including activity photos and lesson plans (RPP/RPH). The findings reveal that both institutions have developed motor programs aligned with the Merdeka Curriculum for Early Childhood Education. Gross motor development is fostered through activities such as gymnastics, movement games, jumping, crawling, running, kicking, and catching a ball. Fine motor development is supported through cutting, folding, pasting, beading, and manipulating small tools. Children’s progress is evaluated using authentic assessments, including observations, anecdotal records, developmental checklists, and portfolios. Challenges identified include limited teacher support, insufficient parental understanding of motor activity safety, and varying developmental levels among children. Despite these obstacles, motor activities significantly enhance children’s body coordination, balance, movement control, courage, concentration, and self-confidence. The study highlights the importance of strong collaboration between schools and parents, along with the provision of a safe and stimulating play environment to optimize early childhood physical motor development